Fundamental failure to think logically about scientific questions: An illustration of tunnel vision with the application of Wason's Card Selection Test to criminal evidence. Issue 4 (8th May 2018) - Rassin, Eric
Summary: Logic and science are in some respects fundamentally different disciplines, in that for example, application of rules of logic can yield conclusions that are at odds with physical reality. Not surprisingly, people have ample difficulty with logical thinking. Nonetheless, in some instances, logical thinking can fuel empirical decision making. In the current research, it was established that applying rules of logic to a particular area of empirical decision making, that is, criminal fact finding, is indeed quite difficult (Study 1). Furthermore, the ability to think logically was found to be associated with superior evaluation of criminal evidence (Study 2). Implications of these findings are discussed.